Urbano-geografsko proučevanje blokovskih stanovanjskih sosesk kot element urbanističnega planiranja - Rebernik, Dejan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
Research about perception and evaluation of living environment by the population of high-rise housing estates in Ljubljana and its potential application in urban planing is presented in the paper. By the use of questionnaire surveys in different high-rise housing estates characteristics of residential location decisions and potential intraurban migrations are defined.
Keywords: Ljubljana; mesta; stanovanjska naselja; stanovanjske četrti; urbana geografija; urbanism; urbanistično planiranje; urbanizem